Efeito da adição de cromo sobre a microestrutura e propriedades termomecânicas em ligas cu-al-be com efeito memória de forma - Cândido, Gemierson Valois da Mota (2010)
This work represents an experimental study on the influence of chromium on microstructure and thermomechanical properties in alloys Cu-Al-Be with shape memory effect. The chemical compositions of these alloys are Cu-11,8Al-0,6Be-XCr; X = 0,1, 0,2, 0,3, 0,5 and 0,05 (wt%). The samples were analyzed by optical microscopy to determine the average grain size, and then subjected to tensile testing at room temperature for values of stress and strain, determination of transformation temperatures of martensitic and austenitic phases via analysis by DSC, which showed lower compared to alloys without Cr and in addition the samples were subjected to hardness testing. From this data it was found that the addition of chromium as grain refiners improved the mechanical properties of the alloy studied.